2020
DOI: 10.3389/fpsyt.2020.00120
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Normalizes Approach–Avoidance Behavior in Women With Borderline Personality Disorder

Abstract: Background: Interpersonal deficits are a core symptom of borderline personality disorder (BPD), which could be related to increased social threat sensitivity and a tendency to approach rather than avoid interpersonal threats. The neuropeptide oxytocin has been shown to reduce threat sensitivity in patients with BPD and to modify approach-avoidance behavior in healthy volunteers.Methods: In a randomized, double-blind placebo-controlled between-subject design, 53 unmedicated women with BPD and 61 healthy women p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
4
16
0
Order By: Relevance
“…No differential effect occurred for angry faces, which is in line with previous findings (Kobeleva et al, 2014;Schneider et al, 2020), although one study found less pronounced approachavoidance behavior in anger-prone women with BPD (Bertsch et al, 2018). Our results are coherent with the idea that psychophysiological reactions to negative effects appear to be intact in BPD (Herpertz et al, 1999;Kuo and Linehan, 2009;Dukalski et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No differential effect occurred for angry faces, which is in line with previous findings (Kobeleva et al, 2014;Schneider et al, 2020), although one study found less pronounced approachavoidance behavior in anger-prone women with BPD (Bertsch et al, 2018). Our results are coherent with the idea that psychophysiological reactions to negative effects appear to be intact in BPD (Herpertz et al, 1999;Kuo and Linehan, 2009;Dukalski et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…This AAT variant revealed no significant difference between patients with BPD and healthy controls. In contrast, Bertsch et al (2018) observed a highly avoidant reaction to angry stimuli, while another study failed to replicate this finding (Schneider et al, 2020), However, Schneider et al (2020 found that approach and avoidance were modulated by oxytocin administration, whereby oxytocin accelerated the avoidant response to angry faces relative to the approach condition toward happy facial expressions in patients with BPD. In another study, no impact of temperamental differences among BPD subtypes on AAT performance was found.…”
Section: Introductionmentioning
confidence: 97%
“…Impairments in the attachment system in BPD, as evidenced by high reports of attachment insecurity (Agrawal et al, 2004) and dysfunction of the oxytocin system (Carrasco et al, 2020), may leave BPD patients without a "filter" to allow them to decide which interactions are safe and rewarding to tune into. Indeed, the administration of intranasal oxytocin was found to normalize approach motivation (Domes et al, 2019) and approach-avoidance behaviour (Schneider et al, 2020) in response to socio-emotional cues in individuals with BPD. However, this increased motivation may not translate into improved social alignment, as the administration of oxytocin has also been found to reduce behavioural synchrony in BPD (Ramseyer et al, 2020).…”
Section: A New Model Of Impairments In Switching Between Self and Other Representations And Interpersonal Attunement In Bpdmentioning
confidence: 99%
“…Mechanistically, a stronger effect of OXT on threatspecific amygdala activation in individuals with a history of CM appears to be rooted in a reinstated top-down regulatory function of the mOFC over the amygdala, thereby emulating a more normative response to social olfactory threat cues in individuals with a history of CM (16)(17)(18)(19)76). Evidence corroborating this interpretation comes from studies demonstrating that OXT reduces threat hypersensitivity in women with Borderline Personality Disorder (90,91) which is frequently associated with CM. Likewise, OXT enhanced the stress-buffering effects of social support in women with more severe CM exposure (51).…”
Section: Discussionmentioning
confidence: 95%